Courtesy Visit to the Embassy of Vietnam expands efforts for new cooperation between UMPSA and Educational Institutions in Vietnam - Nur Ezzati, Mohd Nasir (UMPSA, 2024)
KUALA LUMPUR, 7 May 2024 – A delegation from Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) paid a courtesy visit to the Embassy of Vietnam in Kuala Lumpur as part of a strategic initiative to expand educational cooperation with higher education institutions in Vietnam.